A comparison of novel laparoscopic suturing techniques in single-port surgery. Issue 6 (2nd November 2019) - Terzi, Hasan; Biler, Alper; Turkay, Unal; Kale, Ahmet
Abstract: Objective: To compare the vaginal cuff closure times of a newly developed Turkish-made laparoscopic needle holder (TMLNH) and a Yoon Soon (YS) extracorporeal knot tying technique in the closure of the vaginal cuff during single-port laparoscopic hysterectomy. Material and methods: We retrospectively reviewed a total of 60 consecutive patients who underwent single-port laparoscopic hysterectomy using a TMLNH ( n = 30) or a YS extracorporeal knot tying technique ( n = 30). Results: The patients' demographic data, operative results, and complications were analyzed. Operative time and the time required for vaginal cuff suturing were significantly shorter in the TMLNH group than in the YS extracorporeal knot tying group (60.1 ± 3.2 vs. 77.3 ± 6.0 min, p = .001 and 24.5 ± 3.7 vs. 36.3 ± 3.8 min, p = .001, respectively). The intraoperative and postoperative complications were comparable in both groups. Conclusion: The use of TMLNH for vaginal cuff closure in single-port hysterectomy reduced the operative time and the time required for vaginal cuff suturing. However, both TMLNH and YS extracorporeal knot-tying technique may enable the surgeons to overcome the surgical challenges of SPA surgery.